(3eHOC GdeSGhGI aj GdYbhHI GdMOjI aj GdTQjYI GdESdGejI (B: s (3OQGSI abgjI JMdjdjI ebGQfI JWHjbG Ydi MO GdRfG (B/ s - (3QGaY eMehO MGeO YHOGdQMefs; (3eMehO HdGd egQGf s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2014)
(3hbYJ GdQSGdI aj aUd JegjOj hHGHjf QFjSjf(B: (3NUUfG GdaUd GdJegjOj ddMOjK Yf eYGde GdfXGe GdYbGHj aj Gdabg GdESdGej aj VhA GdebGUO GdNGUI HGdYbhHGJ GdMOjI(B. (3CeG GdHGH GdChd abO JcdefG ajg Yf eHOC GdeSGhGI aj GdYbhHGJ GdMOjI(B: (3hPdc HOA ef GdMOjK Yf GdJWhQ GdJGQjNj deHOC GdeSGhGI HTcd YGe hUhdG Edi eYfGg hCOdI Gdbhd Hg aj Gdabg GdESdGej(B: (3eHjfjf ddbhGYO GdJj jDOj GdCNP HgG aj GdYbhHGJ GdMOjI Edi JMbjb GdeSGhGI GdaYdjI Hjf GdLfGI(B. (3CeG GdKGfj abO JYQVfG ajg ddGSJKfGAGJ GdhGQOI Ydi GdeHOC ShGA eG JYdb efgG HGdEKHGJ Ch HGdJTOjO Ch GdJNaja Ch hba GdJfajP Ch eGcGf PG YdGbI HESbGW GdYbhHI s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdTQjYI GdESdGejI, (B2014s
(3HHdjhLQGajG(B: (3UaMGJ (B409-444s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdTQjYI GdESdGejIs; (3GdEcQGg Ydi GdRfGs; (3GdeSGhGI aj GdMOhOs; (3bhGYO GdeSGhGI GdMOjIs; (3GdTPhP GdLfSjs; (3TgGOI GdfSGA Ydi GdRfGs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdTQjYI GdESdGejIs